Trends in the development of credit relations in the agricultural sector - Гулая, Алла Сергеевна (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2016)
The peculiarities of credit relations use by actorsin the agricultural sector, the analysis of financial support to agricultural producers and directions to optimize interest rate policy of a commercial bank, the use of documentary instruments are suggested. The directions of the increased use of credit relations in the agricultural sector through the provision of state support are proposed.